Upaya Menarik Genarasi Muda untuk Bekerja di Sektor Pertanian: Efforts to Attract Young People to Work in the Agricultural Sector - Salsabila, Alsti Kalica; Rozaki, Zuhud; Wulandari, Retno; Nurlita, Mita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
The interest in pursuing agriculture should be the main reason why young people choose agricultural vocational training, many factors influence this decision. Indonesia is one of the countries that rely on the agricultural sector because of its advantages. However, in recent years, the need for qualified and talented human resources has decreased, especially in the agricultural sector, which will affect the contribution of the young agricultural workforce/young generation to the success of Indonesian agriculture. The objectives of this study are: 1) to find out the factors that affect food security. 2 ) Knowing the important impact of the agricultural sector on food security 3) The importance of the agricultural sector to food security. 4) to determine the perception of the younger generation towards agricultural development in Indonesia. Efforts to increase the interest of the younger generation are carried out in various ways, including by improving education, creating young entrepreneurs in the agricultural sector, and creating incentives to stimulate the interest of the younger generation to work in the agricultural sector.